An investigation of liquid cooled air blower performance for laptop cooling system / Nicholas Pinenn and Jamilah Karim - Pinenn, Nicholas; Karim, Jamilah (Universiti Teknologi MARA, 2019)
This work presents a study on the performance of custom design laptop's cooling system. Differ from existing external cooling solution for laptop which blows slowly ambient air to the laptop's ventilation, this system lowers the ambient air temperature then blows it into the laptop's cooling box and increase its internal air pressure. The internal pressure then used to force the extra air flow into the laptop's ventilation port and into the laptop's internal cooling system. Several tests has been conduct in order to prove the reliability of the design system. The data obtained from the test are analyzed by using numerical method which the new cooling method is giving significant cooling. The cooling system demonstrated the liquid cooled air blower system gives up to 8 percent cooler than stock cooling system and 5 percent cooler when compared with existing on market cooling pad when the CPUs are in continuous stress test.